Evaluation of active wearable assistive devices with human posture reproduction using a humanoid robot*. (18th June 2018) - Ito, Takahiro; Ayusawa, Ko; Yoshida, Eiichi; Kobayashi, Hiroshi
ABSTRACT: This study proposes a quantitative evaluation method for assessing active wearable assistive devices that can efficiently support the human body. We utilize a humanoid robot to simulate human users wearing assistive devices owing to various advantages offered by the robot such as quantitative torque measurement from sensors and highly repeatable motion. In this study, we propose a scheme for estimating the supportive torques supplied by a device called stationary torque replacement. To validate the reliability of this evaluation method by using a humanoid robot, we conducted measurements of human muscular activity during assisted motion. Analysis of the measured muscle activity revealed that a humanoid robot closely simulates the actual usage of assistive devices. Finally, we showed the feasibility of the proposed evaluation method through an experiment with the humanoid robot platform HRP-4 and the Muscle Suit active assistive device. With the proposed method, the supportive effects of the assistive device could be measured quantitatively in terms of the static supportive torque acting directly on the body of a simulated human user. GRAPHICAL ABSTRACT: